3,4 номер,3 вариант

Уточнение вопроса

3,4 номер,3 вариант ​

Подробное решение

3) y(y – 5)(y + 5) – (y + 2)(y² – 2y + 4) = y(y² – 25) – (y³ + 2³) =

= y³ – 25y – y³ – 8 = – 25y – 8

4a) a² – 36b² +a – 6b = (a² – 36b²) + (a – 6b) = (a – 6b)(a + 6b) + (a – 6b) =

= (a – 6b)(a + 6b + 1)

б) 4 – m² + 14mn – 49n² = 4 – (m² – 14mn + 49n²) = 2² – (m – 7n)² =

= (2 – m + 7n)(2 + m – 7n)

в) (x – 4)³ + 27 = (x – 4)³ + 3³ = (x – 4 + 3)[(x – 4)² – 3(x – 4) + 3²] =

= (x – 1)(x² – 8x + 16 – 3x + 12 + 9) = (x – 1)(x² – 11x + 37)

Оставить ответ

Ваш адрес email не будет опубликован. Обязательные поля помечены *